On the mechanism of agglomeration in suspension - Maryam Maghsoodi; Katayoun Derakhshandeh; Zahra Yari (Tabriz University of Medical Sciences, 2012)
Purpose: Agglomeration in suspension is a size enlargement method that facilitates operation of solid processing and preserves the solubilization properties of fine particles. A small quantity of binder liquid is added into a suspension of microparticles, directly in the stirred vessel where the precipitation or crystallization took place. This study deals with the evaluation of the effect of agitation time before and after addition of binder liquid on agglomerates properties in order to give some insights into the mechanism of the formation of the agglomerates. Methods: Carbamazepine is used as a model drug and isopropyl acetate is used as binder liquid. The agglomerates characterization includes the particle size, morphology and density. Results: The results showed that, by increasing the agitation time before addition of binder liquid, smaller agglomerates with less density and irregular forms composed of larger crystals were obtained. However, with increasing agitation time after addition of binder liquid the agglomerates size and density increases and morphology improves. Indeed, by continuing agitation along the course of agglomeration the properties of the particles change gradually but substantially. Conclusion: With optimized agitation time before and after addition of binder liquid, spherical and dense agglomerates can be obtained.